Migrant Workers Rights from a Human Rights Perspective - Rani, Padma (ASIAN REVIEW, 2021)
Migrant workers constitute 59% of the migrant population. Migrants contribute to growth and development in their place of destination, while the place of origin benefits from their remittances and the skills acquired. Migration is here to stay, it has multiple benefits, and it is a fundamental human right to work and move in freedom. The two main approaches to deal with migration-the migration management and the human rights approach. The human rights approach is based on international human rights law. Under international human rights law, all migrants are entitled to respect, protection, and full enjoyment of their human rights, regardless of their migration status. This paper will deal with the provisions for the protection of migrant labour's and examine the provisions by looking at cases of migrant labour. Also, examine the plight of migrant labour during Covid-19 in the light of travel restrictions, loss of employment and stigma.